FDG PET/CT of uncommon cardiac angiosarcoma with bone metastases: a case report - Moreno-Monsalve, Tatiana; Frutos-Esteban, Laura; Navarro-Fernández, Jose Luis; Mohamed-Salem, Laroussi; Castellón-Sánchez, María Isabel; Hernández-Martínez, Ana Cristina; Rodríguez-Locarno, Tomas; Rodríguez-Locarno, Tomas; Contreras-Gutierrez, Jose Fulgencio; Contreras-Gutierrez, Jose Fulgencio (Journal of Cardiology and Cardiovascular Medicine, 2022)
Cardiac angiosarcomas are rare malignant neoplasms with an aggressive clinical course. These are characterized by the absence of specific clinical findings, rapid growth with frequent metastasis at the time of diagnosis, correlated with poor prognosis, and reduced response to treatment. But with early diagnosis, more possibilities for treatment and survival can be provided. We report the case of a young woman diagnosed with right atrial angiosarcoma locally advanced with bone metastases detected by 18F-FDG PET/CT, which revealed distant disease extent at diagnosis, consequently, chemotherapy was started.